Enfermedad cardiovascular asociada a las terapias supresoras de andrógenos utilizadas para el tratamiento del cáncer de próstata: una revisión de alcance (Research, Society and Development, 2022)
Worldwide, prostate cancer (PCa) represents the second leading cause of death from cancer in the male population, and shares many of the risk factors that also predispose to the emergence of cardiovascular diseases (CVD's). The established treatment for PCa involves the use of androgen deprivation therapies, although this strategy is known to induce myocardial injury. The purpose of this text is to discuss the association between CVDs and androgen suppression therapies used for PCa. For this Scope Review, carried out through the PubMed and Science Direct platforms between 2020 and 2022, the descriptors chosen were ''Heart'', ''Therapy'', ''Androgen'' and ''Prostate Cancer'', associated with the boolean operator ''AND''. Inclusion criteria consisted of 1) clinical trials, controlled and randomized trials, reviews and meta-analyses; 2) studies on the association between CVDs and androgen suppression therapies 3) studies that evaluated the damage caused by cardiotoxicity, as well as its management and follow-up and 4) articles in English, Spanish and Portuguese. Exclusion criteria consisted of inadequacies to the topic, case reports and studies with animals, in addition to texts outside the time limit. It was observed that the use of androgen deprivation for PCa can induce adverse cardiovascular repercussions, such as systemic arterial hypertension, heart failure, acute myocardial infarction and stroke. Discontinuation of these drugs and consensus on the threshold of toxicity for these drugs are still controversial topics, as is the choice of cardioprotective therapies.